KONFLIK BATIN DAN NILAI KARAKTER TOKOH UTAMA DALAM NOVEL LOVE, INTERRUPTED KARYA MAYA LESTARI GF SEBAGAI ALTERNATIF BAHAN AJAR SASTRA DI SMA KELAS XII: KAJIAN PSIKOLOGI SASTRA - Kharina Cahya (Universitas Tanjungpura, 2022)
This research has the first objective to describe the physical structure of the novel Love, Interrupted by Maya Lestari GF. Second, describe the inner conflict of the main character Aisha contained in the novel Love, Interrupted by Maya Lestari GF. Third, describe the character values contained in the novel Love, Interrupted by Maya Lestari GF. Fourth, describe the suitability of the novel Love, Interrupted by Maya Lestari GF so that it can potentially be an alternative source as a good literature teaching material at the XII grade high school level.This research is studied by using literary psychology because the theory used is in the form of psychological theory. In this study, the research approach used is a psychological research approach because this study examines the psychological aspects of characters in a literary work in the form of a novel. The results of the first research are the Love Interrupted novel by Maya Lestari GF which has a structure like novels in general. Secondly, in the novel Love, Interrupted, there is an inner conflict that is understood by the character Aisha which can be an experience for the readers. The three Love, Interrupted novels by Maya Lestari GF contain 16 values of character education, namely responsibility, social care, environmental care, love of reading, patient/communicative, appreciating achievement, curiosity, democracy, independence, creativity, hard work, discipline. , tolerance, honesty, religious, and toughness. The four Love, Interrupted novels by Maya Lestari GF have the potential to be used as an alternative source of teaching materials containing literature at the XII grade high school level based on the field of conformity. This suitability field consists of. (1) in terms of psychology, this novel can be taught to high school students of class XII because it has a positive side to the character Aisha. (2) contains terms from Minang language and English in order to develop insight and knowledge for class XII high school students. (3) this novel is able to increase the imagination of high school students in class XII by describing the situation through imaginary sentences or fantasies used by the author. (4) novels foster students' curiosity with stories found in novels.